Peak-bagging and cartographic misrepresentations: a call to correction. Issue 14 (18th July 2021) - Apollo, Michal; Mostowska, Joanna; Maciuk, Kamil; Wengel, Yana; Jones, Thomas E.; Cheer, Joseph M.
ABSTRACT: Tourists put their trust in maps and guidebooks and they expect information within to be accurate. Unfortunately, vital information can often be incorrect such as the accuracy of altitude above sea level. Cartographic misrepresentations and the impact on tourism is the focus of this study. Altitude data from maps, guidebooks and summit signs were compared with professional measurements made by precise Global Navigation Satellite Systems receivers. Findings revealed significant discrepancies in reported peak altitudes ranging from a few and up to several hundred metres. Evidently, some of the highest summits of the mountain ranges are subject to degradation and/or change over time and this underlines cartographic misrepresentations. There are possibly other inaccuracies in scores of popular peaks around the globe and rectifying erroneous information is vital for peak-bagging visitors. The results of this exploratory stud have significant implications for the management and marketing of destinations when a mountain's popularity is based around being the highest .